2010
DOI: 10.1111/j.1476-5381.2010.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

KMUP‐3 attenuates ventricular remodelling after myocardial infarction through eNOS enhancement and restoration of MMP‐9/TIMP‐1 balance

Abstract: BACKGROUND AND PURPOSE Previously,piperazinyl]ethyl]-1, 3-dimethylxanthine (KMUP-3) has been shown to induce aortic smooth muscle relaxation through KATP channel opening and endothelial nitric oxide synthase (eNOS) enhancement. We further investigated whether KMUP-3 protects against myocardial remodelling after myocardial infarction (MI), and whether KMUP-3 increases the expression of eNOS in MI rats. EXPERIMENTAL APPROACHWistar rats were randomly allocated into three groups: MI (n = 10), MI + KMUP-3 group (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…In addition to the stimulation of MMP9 expression by IL6 and other proinflammatory cytokines, previous studies have shown that nitric oxide (NO) inhibited MMP2 and MMP9 expression by smooth muscle cells (Gurjar et al 1999) and enhancement of eNOS expression in rat heart reduced MMP9 expression (Liu et al 2011). Thus, MMP9 expression is associated with endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the stimulation of MMP9 expression by IL6 and other proinflammatory cytokines, previous studies have shown that nitric oxide (NO) inhibited MMP2 and MMP9 expression by smooth muscle cells (Gurjar et al 1999) and enhancement of eNOS expression in rat heart reduced MMP9 expression (Liu et al 2011). Thus, MMP9 expression is associated with endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2, a factor known to mediate ECM degradation during MI (Matsumura et al, 2005) resulting in pathological remodeling via cardiomyocyte anoikis and macrophage infiltration, is endogenously secreted by hMSCs and the activity of hMSC-secreted MMP-2 can be inhibited by treating hMSCs with TNF-α or hypoxia (Lozito and Tuan, 2011). Additionally, MSC secreted factors such as MMP-9 and IL-6, responsible for pathological remodeling and pro-inflammatory responses, respectively, should ideally be maintained at minimum levels as these factors are upregulated in the myocardium during MI (Biswas et al, 2010; Liu et al, 2011). Inhibition of negative factors using antagonists (produced by MSCs) such as TIMP-1 (for MMP-9) and IL-10 (for IL-6) either via intracellular or extracellular targets is one possible strategy for alleviating these effects.…”
Section: Close To the Heart? Relevance Of Msc Paracrine Signaling To mentioning
confidence: 99%
“…The lack of the endothelial hydraulic conductivity (Lp) response in shear stress, and the lack of alignment is due to the decreased phosphorylation of endothelial-derived nitric oxide synthase (eNOS), which leads to decreased NO production [201, 203]. In addition to its role in endothelial alignment, NO plays a role in inhibiting MMP-2 and MMP-9; therefore, the decreased NO levels lead to an increase in these MMPs [204]. These findings indicate that the loss of the glycocalyx due to hyperglycemia in the diabetic retina can mediate increased leukocyte adhesion, decreased NO availability, and increased ROS production and oxidative stress.…”
Section: Microvascular Damage In Drmentioning
confidence: 99%